Effect of diet and physical exercise intervention programmes on coronary heart disease risk in smoking and non-smoking men in Sweden. Issue 2 (April 1996) - Näslund, G K; Fredrikson, M; Hellénius, M L; de Faire, U
Abstract : STUDY OBJECTIVE: To investigate differences between smokers and non-smokers in health behaviour, cardiovascular risk factors, coronary heart disease (CHD) risks, health knowledge, health attitudes, and compliance with a CHD prevention programme. DESIGN: Differences between smokers and non-smokers were studied via medical examinations, questionnaires, physical exercise activity logs, and food record sheets. Data were analysed using univariate and multivariate analyses. The five and 10 year CHD risks were assessed using the Framingham CHD risk estimate. SETTING: The Karolinska Hospital, Stockholm, and Sollentuna Primary Health Centre, Sollentuna, Sweden. PARTICIPANTS: The analyses were based on 158 healthy smoking and non-smoking men aged 35-60 years with raised cardiovascular risk factors who enrolled in controlled, randomised six month diet and exercise programmes. MAIN RESULTS: Discriminant analysis suggested that smokers, compared with non-smokers, were characterised by a higher alcohol energy percent, lower HDL cholesterol concentration, lower systolic blood pressure, and a higher plasminogen activator inhibitor-1 (PAI-1) value. Knowledge of the risk factors for CHD was not a discriminating factor. Both smokers and non-smokers increased the exercise taken, improved their diet, and lowered their CHD risk. Before, as well as after the intervention, smokers had a higher CHD risk than non-smokers. CONCLUSIONS: The best CHD prevention action that could be taken by smokers would of course be to quit smoking. Those who cannot stop should be encouraged to improve their diet and increase the amount of physical exercise they take in order to reduce the health hazards of their smoking behaviour.